Earnings Management, Good Corporate Governance, Size of Public Accounting Firm on The Integrity of Financial Report - Khayatul Izzah; Nawirah Nawirah (InFestasi, 2021)
Implementation of Good Corporate Governance (GCG) which is believed to minimize the occurrence of fraud to achieve the integrity of financial report, GCG is proxied by institutional ownership, independent commissioners, and audit committees. Public Accounting Firm (KAP) as a variable which is an external auditor as an intermediary if there is a difference of opinion with the company's internal parties. The purpose of this study is to find out the effect of Earnings Management, Institutional Ownership, Independent Commissioners, Audit Committees, Size of Public Accounting Firms on the Integrity of Financial Report in mining companies. The researcher uses mining companies in Indonesia for the 2015-2019 period as the population with 22 companies as the research samples. Panel data analysis Eviews 9.0 software is used as a research method. The results of this study prove that the variables have a significant effect are the audit committee, meanwhile earnings management, institutional ownership, independent commissioners, size of public accounting firm on the integrity of the financial report have no significant effect.